Reconceptualization of the Relationship between Formative Assessment and Summative Assessment - Jian, Huang (EDUCARE, 2015)
ABSTRACT: Formative Assessment (FA) and Summative Assessment (SA) constitute two indispensable parts of any effective assessment system. As FA was proposed as an alternative to SA, there has been an academic concern about their relationship since the birth of these two concepts. Although many well-known studies have been carried out for FA, or, SA, or both, there has been contrasting views and misunderstandings about the relationship between FA and SA. It is argued in this paper that the confused relationship between FA and SA stems from the fact that it is either conceptualized from the perspective of function or from the perspective of process alone. The relation between FA and SA is very fine, far from clear-cut and a clarified relation between them is necessary for both our right understanding of FA and SA as well as the realization of the balance between FA and SA in practice as advocated by many educational policies. This paper aims to: (1) carry out an analysis of the function-based perspective and process-based perspective; and (2) re-conceptualize the relationship between them by combining the two perspectives together. The study results suggest that: (1) both FA and SA are, first of all, assessment and therefore share the same neutral assessment processes of elicitation of learning evidence, interpretation of evidence, and use of assessment results; (2) the purpose governs the how each process should be carried out and the extent to which summative or formative function is performed depends the how the processes are carried out; and (3) formative use of SA is more feasible than summative use of FA in practice.KEY WORDS: Relationship between formative assessments, function perspective, process perspective, contrasting views, misunderstandings, and re-conceptualize.About the Author: Huang Jian is a Lecturer at the School of Foreign Studies CUFE (Central University of Finance and Economics) in Beijing, China. Address: 39 South College Road, Haidian District, Beijing, People Republic of China, 100081. E-mail: summerofhj@sina.comHow to cite this article? Jian, Huang. (2015). âReconceptualization of the Relationship between Formative Assessment and Summative Assessmentâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.1-10. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (February 16, 2015); Revised (April 21, 2015); and Published (August 25, 2015).